Bortezomib treatment followed by a second non-myeloablative allogeneic stem cell transplant in two previously autografted patients with multiple myeloma relapse - D Mattei; N Mordini; R Vigna Taglianti; B Bruno; D Rapezzi; A Gallamini (Haematologica, 2005)
We report two cases of multiple myeloma relapse and progression following a combination of autologous stem cell transplantation and non-myeloablative allogeneic stem cell transplantation. After failure of donor lymphocyte infusions and thalidomide salvage therapy, the patients were treated successfully with bortezomib and eventually underwent a second non-myeloablative allogeneic stem cell transplantation.